Mathematical modelling of mass transfer during osmotic dehydration of seedless guava (Pisidium guajava L.) cubes - Ganjloo, Ali; Abdul Rahman, Russly; Bakar, Jamilah; Osman, Azizah; Bimakr, Mandana (Faculty of Food Science and Technology, Universiti Putra Malaysia, 2011)
The present work aimed to study kinetics of osmotic dehydration of seedless guava in terms of solid gain and water loss, which was evaluated at three sucrose concentration levels (30, 40 and 50% w/w), three temperature levels of osmotic solution (30, 40 and 50°C) for 240 min. The experimental data was fitted to different empirical kinetic models including Peleg, Page and Azuara. Determination of coefficient (R 2 ), root mean square error (RMSE) and mean relative deviation modulus (E) were used for determination of the best suitable model. The present work shows that the Peleg empirical model satisfactorily described the dehydration kinetics with the highest R 2 ( > 0.95) and the lowest RMSE ( < 0.003) and E ( < 5.20%). Moreover, the effect of solution concentration and temperature was also studied and it was found that initial water loss and solid gain are related to solution concentration and temperature whereas equilibrium contents are related to sucrose concentration. From the experimental data it is possible to estimate the equilibrium content of water and solid.